Bone mineral density is negatively correlated with ulcerative colitis: a systematic review and meta‐analysis. Issue 1 (18th February 2020) - Zhou, Tianyu; Pan, Jiaqi; Lai, Bin; Cen, Li; Jiang, Wenxi; Yu, Chaohui; Shen, Zhe
Abstract: Background: Newer epidemiological studies suggest that the incidence of ulcerative colitis might be increasing rapidly. Furthermore, osteoporosis in ulcerative colitis patients has gained great attention, but the epidemiologic evidence remains controversial. Therefore, a meta‐analysis was performed to explore the association between bone density and ulcerative colitis. Methods: Two investigators used PubMed, EMBASE and the Cochrane Library databases to identify all studies published before August 2019. Depending on the outcomes, investigators divided these studies into four groups (OR, SMD [BMD], SMD [z‐score] and SMD [t‐score]). To address the use of steroids, which is a major confounding factor in this analysis, another subgroup analysis of studies of steroid‐free patients was conducted. Additionally, heterogeneity, sensitivity and stratified analyses were also performed. Results: A total of 13 cross‐sectional studies that involved 1154 participants were included in the present meta‐analysis, and three of them were included in the steroid‐free subgroup analysis. The pooled OR was 6.41 (95% CI 2.59–15.87) and the pooled SMD (BMD), SMD (t‐score) and SMD (z‐score) were − 0.24 (95% CI − 0.44 to − 0.04), − 0.55 (95% CI − 0.72 to − 0.37), and − 0.38 (95% CI − 0.56 and − 0.19), respectively. Since steroids are a significant confounder, the pooled SMD of the steroid‐free subgroup was − 0.55 (− 0.85 to − 0.25), which revealed a strong negative relationship between bone density and ulcerative colitis in steroid‐free patients. Additionally, other subgroup analyses also revealed a strong relationship. Conclusions: This meta‐analysis provides evidence for the potential association between ulcerative colitis and decreased bone density. It is essential for clinicians to consider bone mineral density in ulcerative colitis patients regardless of steroid‐therapy.